2011
DOI: 10.3923/pjbs.2011.688.692
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Levels of Trace Metal from Two Fish Species Harvested from Treated Waste Water in Pretoria, South Africa

Abstract: The persistent problem of water scarcity with the ever increasing demand of water has necessitated the reuse of effluent in agriculture. The present study evaluated the reuse of treated waste water and bioaccumulation properties of two fish species from a manmade lake. Trace metals content of two fish species: Clarias gariepinus and Cyprinus carpio and levels of trace metals from waste water in the lake where the fish species were harvested were determined by Inductive Couple Plasma-Optical Emission Spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Also Radhakrishnan (2010) observed that levels of metals (Fe, Cu, Zn, Mn, Cr) in Heteropneustes fossilis gill, liver and muscle were higher than in water. Olowoyo et al (2011) reported that concentrations of Zn, Fe, Mn, Cr, Ni, Cu, Pb in C. carpio and Clarias gariepinus liver, gill, muscle, bone were higher compared to the levels of these metals in water and concluded that it was a result of bioaccumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also Radhakrishnan (2010) observed that levels of metals (Fe, Cu, Zn, Mn, Cr) in Heteropneustes fossilis gill, liver and muscle were higher than in water. Olowoyo et al (2011) reported that concentrations of Zn, Fe, Mn, Cr, Ni, Cu, Pb in C. carpio and Clarias gariepinus liver, gill, muscle, bone were higher compared to the levels of these metals in water and concluded that it was a result of bioaccumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors (e.g., Kraal et al 1995; Jacobson and Reimschuessel 1998; McGeer et al 2000; Celechovska et al 2007; Ghedira et al 2010; Radhakrishnan 2010; Shao et al 2010) showed that the highest concentrations of copper were noted in fish liver. Liver being main detoxification site in organism is also an organ that bioaccumulates toxic substances, and thus, it usually shows higher concentrations of metals than another tissues (Allen 1995; Olowoyo et al 2011). Couture and Kumar (2003) suggested that copper and cadmium concentration led to an up-regulation of liver protein metabolism, presumably at least in part for the purpose of metals detoxification.…”
Section: Discussionmentioning
confidence: 99%
“…Mn was found to be the lowest concentration of heavy metals across the three station of the river, ranges from 0.44±0.03 a mg/kg, 0.33±0.02 a mg/kg and 0.43±0.03 a mg/kg and they all have the same significant differences across the three station of the river, this finding is supported by the report of Oluseye et al (2012), who also recorded low concentration for Clarias garienpinus and Oreochromis niloticus. However, Mn fish helps in fish reproduction and normal functioning of nervous system (Olowoyo et al, 2011). the findings of this research shows that concentration of Mn was significant at p<0.05.…”
Section: Fish Samplesmentioning
confidence: 53%
“…The concentration could be attributed to bioaccumulation of pollutant over a long period of time from other pollutant source. However, low concentrations of Pb inhibit inactive transport mechanisms involving ATP and also suppress cellular oxidation-reduction reaction (Olowoyo et al 2011).…”
Section: Sediment Samplementioning
confidence: 99%